1996
DOI: 10.1083/jcb.133.5.929
|View full text |Cite
|
Sign up to set email alerts
|

Demonstration of a dynamic, transcription-dependent organization of pre-mRNA splicing factors in polytene nuclei.

Abstract: Abstract. We describe the dynamic organization of pre-mRNA splicing factors in the intact polytene nuclei of the dipteran Chironomus tentans. The snRNPs and an SR non-snRNP splicing factor are present in excess, mainly distributed throughout the interchromatin. Approximately 10% of the U2 snRNP and an SR nonsnRNP splicing factor are associated with the chromosomes, highly enriched in active gene loci where they are bound to RNA. We demonstrate that the splicing factors are specifically recruited to a defined g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

1996
1996
2014
2014

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(37 citation statements)
references
References 63 publications
2
34
0
Order By: Relevance
“…Consistent with previous evidence for cotranscriptional processing of pre-mRNA obtained in noninfected cells (Beyer and Osheim 1988;LeMaire and Thummel 1990;Wu et al 1991;Xing et al 1993;Bauren and Wieslander 1994;Zhang et al 1994;Tennyson et al 1995;Bauren et al 1996;Huang and Spector 1996;Neugebauer and Roth 1997), in situ evidence suggests that splicing of Ad mRNAs occurs cotranscriptionally. Namely, spliceosome components including snRNPs and non-snRNP splicing proteins are recruited to the sites of viral mRNA synthesis (Pombo et al 1994;Bridge et al 1995;Gama-Carvalho et al 1997, 2003.…”
Section: Resultssupporting
confidence: 85%
“…Consistent with previous evidence for cotranscriptional processing of pre-mRNA obtained in noninfected cells (Beyer and Osheim 1988;LeMaire and Thummel 1990;Wu et al 1991;Xing et al 1993;Bauren and Wieslander 1994;Zhang et al 1994;Tennyson et al 1995;Bauren et al 1996;Huang and Spector 1996;Neugebauer and Roth 1997), in situ evidence suggests that splicing of Ad mRNAs occurs cotranscriptionally. Namely, spliceosome components including snRNPs and non-snRNP splicing proteins are recruited to the sites of viral mRNA synthesis (Pombo et al 1994;Bridge et al 1995;Gama-Carvalho et al 1997, 2003.…”
Section: Resultssupporting
confidence: 85%
“…Osheim et al 1985;Kiseleva et al 1994;Bauren et al 1996) support a model in which splicing factors accumulate at endogenous sites of transcription where splicing occurs. The detection of a high concentration of any given factor at a gene is likely to depend on the affinity of the factor for the RNA synthesized at the gene.…”
Section: Discussionmentioning
confidence: 99%
“…This has led to the suggestion that speckles contain the highest concentrations of splicing factors--perhaps serving as storage or assembly sites--and that lower concentrations may be present where splicing occurs (Fakan et al 1984;Fakan 1994;Xing et al 1995;Huang and Spector 1996). Interestingly, SR proteins and splicing snRNPs are detected at active sites of transcription on polytene and lampbrush chromosomes, which are particularly well-suited for cytological observation (Roth et al 1989(Roth et al , 1991Champlin et al 1991;Amero et al 1992;Kim et al 1992;Wu et al 1993;Bauren et al 1996). Although splicing factors accumulate at very large and highly active viral transcription units in infected mammalian cells (cf.…”
mentioning
confidence: 99%
“…SnRNP and several nonsnRNP splicing factors accumulate at both perichromatin fibrils and interchromatin granules, raising the possibility that splicing of precursor RNA may occur at these locations. Previous work suggests that some splicing of transcripts occurs at the site of transcription (Beyer and Osheim, 1988;Zhang et al, 1994;Baur6n and Wieslander, 1994;Baur6n et al, 1996;Huang and Spector, 1996); but splicing has also been observed to occur posttranscriptionally (Baur6n and Wieslander, 1994). Although splicing factors are present in the coiled body, this structure is not thought to be directly involved in the splicing of RNA, but may rather be involved in some aspect of the trafficking of splicing factors .…”
mentioning
confidence: 99%